II-10 HO-1 expression in monocytes might contribute to increased ros levels during phagocytosis in lupus nephritis patients. (31st August 2016) - Cuitino, Loreto; Crisostomo, Natalia; Vega, Fabian; Schmidt, Camila B; Torres, Andy; Kalergis, Alexis M; Llanos, Carolina
Abstract : Background: Systemic lupus erythematous (SLE), an autoimmune disorder, is associated with autoantibody synthesis and inflammation. Although Lupus Nephritis (LN) is a complex manifestation of SLE that affects about 50% of patients, the cascade of events leading to glomerular damage develops its own dynamic of progression. Our group has studied the potential role of Heme Oxygenase-1 (HO-1) in the modulation of innate immune cells during SLE onset and the progression of disease, and its therapeutic potential. We have recently shown that HO-1 mRNA and protein are decreased in CD14+ monocytes from SLE patients. Also, we showed that CO exposure reduces CD11b+ cells in the spleen of FcγRIIb knockout mice, and that both CO and CoPP, a HO-1 inducer, delays the onset of proteinuria in these mice. Here we have evaluated HO-1 expression, phagocytosis levels and reactive oxygen species (ROS) production in purified monocytes from peripheral blood of LN patients and healthy controls. Materials and methods: SLE patients with proliferative LN confirmed by renal biopsy (Class III, IV or V ISN/RPS) were recruited at Hospital Clinico of PUC. All individuals signed an informed consent form. This study was approved by the Research Ethics Committee of PUC, School of Medicine. Monocytes were purified using pan-monocytes MACS kit. HO-1 expression was measured by FACS and the mean intensity of fluorescence (MFI) was determinate. The phagocytic ability was measured by FACS and the total phagocytosis was calculated as the percentage of cells with engulfed beads. ROS was measured using CellRox Kit and the MFI was calculated. Results: We found that monocytes purified from LN patients show significant differences as compared to healthy controls in all the parameters analysed. HO-1 expression was decreased in monocytes from LN patients. The phagocytosis level was increased in monocytes of LN patients independently of the serum used to opsonize the beads (Control or autologous serum). The most important difference was observed in the percentage of monocytes that phagocyte 4 or more beads. The basal ROS level was higher in monocytes of LN patients, reaching a value similar to the monocytes of healthy controls treated with TBHP, a ROS inducer. Conclusions: Although our preliminary findings show that LN monocytes display increased phagocytosis, the basal levels of ROS are elevated in LN when compared to healthy controls. We propose that this increment could be modulated by HO-1 levels, which are decreased in LN monocytes. FONDECYT N° 1150173.